Presupuesto financiero para la empresa transporte Ararat S.A.S del municipio de Candelaria (2024)
The financial budget provides a detailed plan of expected revenues, expenses and cash flows during a specific period. This allows the organization to establish clear financial objectives and develop strategies to achieve them. In this sense, this work was carried out with the purpose of proposing a financial budget for the company Transporte Ararat S.A.S., located in Candelaria, which allows the implementation of action plans that favor decision making.